TOWARDS A SEMANTIC-BASED SEARCHING IN A WEB APPLICATION FRAMEWORK FOR AN IMPROVED DEVELOPMENT PRODUCTIVITY AND USABILITY - Imran Harith Azmy; Azri Azmi; Nazri Kama; Hazlifah Mohd Rusli; Asyraf Wahi Anuar, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The increasing usage and advancements of Web Application technologies have resulted in the demand for quick development of high-quality web applications. The situation resulted to the emergence of various frameworks and methods for a rapid application development of web applications, such as code generators. Conventional code generators generally anchor basic and generic operations of create, read, update and delete (CRUD) for efficient development through automation by eliminating redundancy and unnecessary work during coding. However, as technologies and use cases of web applications progress, information retrieval or 'search' became one of the most common features of a web application apart from the very basic CRUD-related functions. A literature review process and analysis of existing web application console framework has been done towards the proposal of solution. We proposed incorporating the search feature into code generators for rapid web application development of the CakePHP framework. Hence, an architecture of the new framework has been presented in this study for future developments that aims to enhance usability and efficient software developments.